Suceeding in applied calculus : - Gordon, Warren B. (Thomson Brooks/Cole, 2007)
Get a better grade with "Succeeding in applied calculus algebra essentials" and its accompanying online learning tool! This quick, easy-to-use resource provides a "just-in-time" algebra review for only those algebra topics that are most essential to the study of applied calculus. Designed to help you succeed in calculus, this mathematics text provides you with examples that include alternative solutions and common mistakes so that you can easily identify where you have made an error. A quick reference guide in the front cover, pre-tests, and post-tests save you time by helping you figure out what you need to review so that you can take your exams with confidence. Use your access to the CengageNOW chapter-by-chapter tutorial website to master problem solving and get step-by-ste assistance in completing your assignments.